GAMBARAN KEBIASAAN MEROKOK DI INDONESIA BERDASARKAN INDONESIA FAMILY LIFE SURVEY 5 (IFLS 5) - Salsabila, Nisa Nisrina; Indraswari, Noormarina; Sujatmiko, Budi (Jurnal Ekonomi Kesehatan Indonesia, 2022)
The characteristics and patterns of smoking behavior are very important data to develop smoking control programs in Indonesia. However, until now there is no comprehensive and systematic data that represents all Indonesian people. This study aims to determine smokers, smoking habits, and smoking addiction in smoking habits in Indonesia based on IFLS 5. Using cross-sectional descriptive using IFLS 5 data. The research subjects are residents aged 15 years and over with a total of 12,591. The results show that smokers in Indonesia are mostly male (95%), only elementary school graduates (35%), work (80%), have a low economy (79%), and live in urban areas (57%). 46% started smoking as a teenager with the type of cigarette that is often used is filtered kretek cigarettes. The median value of cigarettes consumed is 12 cigarettes/day by spending Rp. 11,000.00/purchase and Rp.56,000.00/week. 46% of smokers smoke >60 minutes after waking up, 68% find it difficult to stop smoking in prohibited places, 37% of heavy smokers do not smoke in the morning, 21% smoke immediately after waking up and 22% of smokers will continue to smoke when sick. This condition shows the poor smoking behavior of Indonesian people. So, it is necessary to intervene in the form of comprehensive education both personal and/or community in groups with these demographics and characteristics.